Effective Communication Results in Effective Leadership - Theresa Olivia Marbun; Piterson Antarani; Monica Amallia Putri (PT Mattawang Mediatama Solution, 2023)
A leader in their leadership must have the ability to build relationships among people. It is the core of fostering motivation, innovation, creativity, inspiration, dynamism, mutual respect, support, and responsibility that can be cultivated through communication. Effective communication is important to the organization’s efforts to achieve its goals. Organizations often need help in achieving goals due to ineffective communication factors. In this case, effective communication skills are required. This study aims to obtain information regarding the effective communication to produce effective leadership. A literature review is conducted to explore much information about effective leadership and communication. Data collection methods were through collecting data from articles related to effective leadership and communication. Inclusion criteria were from original articles, literature reviews, and review papers on effective communication resulting in effective leadership. Effective communication can result in effective leadershi. Effective leader development and leadership behaviour are the major concerns in all types of organizations. Effective communication is an important part of the organization to achieve goals. Various obstacles faced within an organization require communication efforts in the organization as a reciprocal relationship. Communication plays a role in delivering messages to other parties and serves as a socio-psychological adhesive, especially in an organization that seeks synergistic cooperation. In this case, the character of effective communication is required. Effective communication requires two-way communication and reflects an equal partnership between different sources. Community empowerment is intended so that all parties are interconnected and not divided by each other. Communication can strengthen the resolution of issues related to cultural differences so as not to damage relationships despite differences. With effective communication, partnership relationships can be established in an effort to achieve common goals.